Early caffeine therapy decreases bronchopulmonary dysplasia but might increase mortality in preterm infants? a systematic review and meta-analysis - Ma, Juan; Chen, Long; Mu, Kaihong; Tang, Shifang; Shi, Yuan (Frontiers in Pediatrics, 2025)
ObjectivesTo assess the effectiveness of early vs. late caffeine therapy for bronchopulmonary dysplasia (BPD) in infants.MethodsPubMed, Embase, Web of Science, and Cochrane databases were searched up to October 2024. Studies comparing early and late caffeine therapy for BPD in infants were included. The primary outcomes were the incidence of BPD, severe BPD, and mortality.ResultsEleven studies (1 RCT and 10 cohorts) with 64,749 patients (34,175 early and 30,574 late) were included. Meta-analysis revealed a significantly lower incidence of BPD (OR: 0.67; 95% CI: 0.56, 0.79; P < 0.00001) but higher mortality (OR: 1.20; 95% CI: 1.12, 1.29; P < 0.00001) in the early group. Subgroup analysis showed a significant difference in BPD incidence in retrospective studies (OR: 0.57; 95% CI: 0.44, 0.74; P < 0.0001), but not in prospective studies (OR: 0.84; 95% CI: 0.44, 1.61; P = 0.61). No significant difference was observed in severe BPD incidence (OR: 0.89; 95% CI: 0.34, 2.35; P = 0.81).ConclusionsEarly caffeine therapy may reduce BPD incidence but increase mortality risk in infants. More large-scale, prospective studies are needed to further evaluate the efficacy of early vs. late caffeine therapy for BPD.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=474351, PROSPERO (CRD42023474351).